Aeronautical Telecommunications: Juridical Nature, Regulatory Regime and Types of Delegation - Feitosa, Fernando Barbelli (Law, State and Telecommunications Review, 2013)
Purpose ”“ This paper examines the juridical nature of aeronautical telecommunications and the Union power to delegate them. Methodology/approach/design ”“ It follows the method of descriptive and inductive logic, juxtaposing the Brazilian legal framework against its actual implementation toward a proposal of an appropriate delegation model. Findings ”“ Among the findings, aeronautical telecommunications are scarcely studied in the legal literature. As a public service under the Union’s legislative and administrative powers, it represents a keystone element for aeronautical navigation and security, but they are also affected by regulation of the telecommunications sector as telecommunications services (art. 21, XI and XII c, of the Constitution of the Federative Republic of Brazil). Practical implications ”“ Considering the legal command that allows aeronautical telecommunications provision by public or private specialized entities (art. 47 and art. 48, sole paragraph of the Brazilian Aeronautics Code), such service should follow the trend of privatization of public airports, by being delegated separately from the airport infrastructure on a vast scale, with a clear definition of the appropriate juridical regime (concession or authorization). Originality/value ”“ This paper encourages legal studies to go deep into the topic of aeronautical telecommunications and suggests a public policy for the nowadays privatization of airports and their ancillary aeronautical telecommunications services.